The risk factors and outcome of early identified acute kidney injury among critically ill obstetric patients - Abd El-Hafez, Amal; Mahjoub, Asmaa; Ahmad, Eman (International Journal of Advanced Nursing Studies, 2017)
Background: Acute kidney injury (AKI) is one of the most challenging and serious complications of pregnancy and postpartum period that facing critical care nurses in Intensive Care Unit (ICU). Having a uniform standard for identifying and classifying AKI would enhance critical care nurses’ ability to recognize these patients and leading to better outcomes.Objective: This work aimed to explore the risk factors and outcome of early identified acute kidney injury of critically obstetric patients in Obstetric ICU. Design. A descriptive cross sectional research design was used in this study. Participants: A total sample of 338 women admitted to Obstetric ICU at Woman Health Hospital, Assiut City, Egypt. Method: Three tools were used.Tool I was developed by the researcher and included demographic and obstetric history, lab parameters, complications and outcomes arising from AKI. The Sequential Organ Failure Assessment (SOFA) score as tool II to determine the extent of a patient's organ function or rate of failure. Measurement of serum creatinine and urine output were used to early identify AKI stages according to Acute Kidney Injury Network (AKIN) Criteria (tool III). Results: The prevalence of AKI among obstetric patients admitted to obstetric ICU was 10.1%; of them 52.9% needed renal replacement therapy and the mortality rate was 29.4%. Postpartum hemorrhage was the most common cause of AKI and its prevalence was 41.2%. It was also found that 74.5% of AKI patients developed complications. Conclusion: AKI complicated 10.1% of total admitted women to the OICU in the studied period. Postpartum hemorrhage represents the most prevalent risk factors with a highly significant SOFA score compared to other risk factors as sever preeclampsia, eclampsia, HEELP & APH with acute fatty liver.